DEVELOPMENT OF A SALES ACCOUNTING INFORMATION SYSTEM TO IMPROVE THE ACCOUNTABILITY OF FINANCIAL STATEMENTS AT THE COMPANY PT. CAHAYA PASIFIK RAYA TULUNGAGUNG - Selfima Muavida; Novi Khoiriawati (SEAN Institute, 2023)
This research aims to describe how the application of sales accounting information systems, while analyzing the advantages and weaknesses of the application, as well as provide suggestions for the development of accounting Information Systems in PT. Cahaya Pasifik Raya. This study uses a qualitative descriptive approach. Data collection techniques using interviews and documentation. Data analysis is done using the Milles and Huberman methods. The results of the research showed that the information system of sales accounting in PT. Cahaya Pasifik Raya involves the function of the sales order section, cash part, sales order part, credit part, packaging part, warehouse part, invoice part, and accounting part. From the SIA that has been carried out there are weaknesses such as recording payments still using manual sales recording sales with manual which causes croscek or re-matching of the total sales with the total goods carried. Then in the credit billing procedure is not separated between the billing part and the marketing part. The development of PT. Cahaya Pasifik Raya involves sales ordering functions, cash, packaging parts, warehouse parts, invoices, accounting, as well as managers.